Scientific Advancements in Illegal Drugs Production and Institutional Responses: New Psychoactive Substances, Self-Harm, and Violence inside Prisons - Rocco D'Este (Institute of Labor Economics (IZA), 2022)
Incarceration is a crucial part of the scholarly analysis of crime, but what happens inside penal institutions largely remains a 'black box' (Western, 2021). This paper studies the impact of the new psychoactive substances (NPS) epidemic within prisons. NPS are powerful addictive chemical compounds that mimic the pharmacological effects of conventional drugs of abuse (CDA) but avoid classification as illegal and detection in standard drug tests. To conduct the analysis, I have assembled a novel establishment-by-month database of all England and Wales prisons from 2007 to 2018 including information on drugs seizures, random mandatory drug test results, various measures of harm, violence, and causes of death. I first document a large increase in NPS availability and an alarming correlation with the steep rise in harm and violence behind bars. I then evaluate the impact of the Psychoactive Substances Act 2016, a supply-side intervention aimed at inhibiting the proliferation of NPS. The analysis exploits cross-prison variation in the initial size of the drug market and shows high-intensity NPS trafficking prisons experienced a sustained but partial reduction in NPS availability, limited substitution toward CDA, and a rise in violence, self-harm, and suicides following the law. Collectively, the findings suggest unwarranted responses to government interventions may be amplified within penal institutions and that new challenges stemming from scientific advances in illegal drugs production should be addressed through systemic interventions that also consider the demand for addictive substances.
Keywords: I18; K14; K42; 330; illegal drugs; new psychoactive substances; prisons; violence; self-harm; supply-side intervention